Do Causal and Concessive Connectives Guide Emotional Expectancies in Comprehension? A Double-Task Paradigm Using Emotional Icons. Issue 8 (17th November 2017) - Morera, Yurena; León, José A.; Escudero, Inmaculada; de Vega, Manuel
Abstract : Continuity and discontinuity are sometimes marked in discourse by means of connectives. This study tested for the first time whether causal and concessive connectives induce expectations of emotional continuity and discontinuity, respectively. Using a novel double-task paradigm, participants first listened to an antecedent clause with a causal or concessive connective (" Because / Although the pupil studied a lot…"), followed by an emotional icon (emoticon), which could match or mismatch the emotional valence of the antecedent. In Experiment 1 participants had to choose the best continuation for the antecedent clause ("he passed" vs. "he failed" the exam) and then identify the emoticon previously shown. In Experiment 2 they had to judge a perceptual feature of the emoticon before performing the consequent choice task. For causal connectives the congruence between the antecedent and the emoticon valence facilitates the consequent choice task (Experiment 1 and Experiment 2) and the emoticon recognition task (Experiment 1) but not the early perceptual judgment task (Experiment 2). This means that causal connectives promote emotional valence continuity at the stage of meaning integration processes. By contrast, concessive connectives do not induce emotional continuity expectancies. In addition, performance in causal positive antecedents and in concessive negative antecedents was more efficient than in the contrasting conditions, suggesting strong emotional biases for these connectives.